(untitled) (African Journal of Biomedical Research, 2023)
Cancer ranks as the second largest cause of death globally. However, little is known about the challenges, coping mechanisms, and social support among this vulnerable group in Nigeria. This study identified the challenges, coping mechanisms, and social support among cancer patients attending the oncology clinic at the University of Nigeria Teaching Hospital Ituku-Ozalla, Enugu State. This was a descriptive cross-sectional study on 124 conveniently selected cancer patients. A researcher-developed questionnaire about the patients’ challenges, coping mechanisms, and social support was used to gather data. Data was analyzed using frequency, percentages, mean and standard deviation and presented in tables. The result showed that the major challenges of the respondents were severe pains and altered body image (92.7%), long waiting hours to be seen by the doctors (91.9%), and lack of finance to keep up with the treatment regimen (86.3). Coping strategies adopted by respondents were fervent prayers and religious activities (3.61±0.68), dieting and maintaining a healthy lifestyle (3.57±0.70), and having a fighting spirit (3.14±1.14). The major sources of social support were family (3.70±0.60), and spouse (3.36±1.03). The highest forms of support were emotional (3.66±0.60), physical (3.65±0.57) and financial (3.02±0.82) support. The majority of the patients face considerable challenges, adopted fervent prayers and religious activities, dieting and maintaining a healthy lifestyle as a coping strategies. Also the major social support identify among this group is from their family. It is therefore recommended the health care provider should increase family involvement in patients care and also enhance spiritual care.